Nilai Pendidikan Agama Hindu Dalam Lontar Putru Pasaji - Ida Bagus Putu Eka Suadnyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Literary works such as lontar, parwa, kakawin, and gaguritan have an honorable and functional place in Balinese Hindu society. These literary works are not only recognized for their beauty, but also have the virtues contained in them. This study was conducted to determine the educational values contained in Lontar Putru Pasaji. This type of research is qualitative with a design method with data sources derived from primary data and secondary data. Data collection begins with the study of the text then conducts interviews, then the data is analyzed by checking the validity of the data. The results of the study found that Lontar Putru Pasaji had Hindu religious education values contained in it, namely, a) Tattwa education values, b). Value of Religious Education c). Value of Ethics Education, d). Yadnya Educational Value.